Tailoring Pore Shapes of Catalysts for Diesel Hydrodesulphurization - Guo, R.; Shen, B.X.; Fang, X.C.; Yang, C.M.; Peng, C. (Asian Journal of Chemistry, 2014)
In order to remove macromolecular sulfides with strong steric effects, a new type of alumina support was developed. The pore structures of the alumina supports were optimized by adjusting the aging time, pH levels and peptizing agent during the synthesis process and the extrusion. For study the influence of the new supports on the hydrodesulphurization catalytic property, the pore structure and acidity of the supports were analyzed. The difference of the acidity distribution was characterized by the NH3-temperature programmed desorption and pyridine-temperature programmed desorption. The acidity levels of NH3-temperature programmed desorption didn’t show obvious change. While the acidity levels of pyridine-temperature programmed desorption of the new support containing clearer pores was higher than that of the conventional supports. This result indicated the new supports favored the absorption of large molecules. Furthermore, the newly catalysts showed a higher desulphurization degree, which led to higher activity.